THE EFFECTS OF LABELING TOWARD BEHAVIOR IN THE NOVEL CONVENIENCE STORE WOMAN BY SAYAKA MURATA - Kristiana, Maria; Jepri (Faculty of Letters Universitas Balikpapan, 2026)
This study aims to analyze the effects of labeling on behavior depicted in the novel Convenience Store Woman by Sayaka Murata. The objectives in this research are; 1) to find out the forms of labeling found in the novel Convenience Store Woman by Sayaka Murata and 2) to describe the forms of labeling affect behavior in the novel Convenience Store Woman by Sayaka Murata. Specially, this study aims to identify the various forms of labeling present in the novel and evaluate how those forms of labeling affect the behavior of the main character in the novel. The researcher uses psychology of literature approach analysis with the theories of labeling by H. S. Becker and behavior by B. F. Skinner. The methodology used in this study adopts a qualitative descriptive approach, drawn from the data collected from various excerpts extracted from the novel. Overall, this research study aims to provide insights into the significance of labeling and its effects on behavior. tHE the paper contributes to ongoing scholarly work related to labeling theory. Understanding the role of labeling in shaping behavior has always been essential in various fields, and this study directly adds value to this area of knowledge.